Unveiling the state of the art: a systematic review and meta-analysis of paper-based microfluidic devices - García-Azuma, Rodrigo; Werner, Karen; Revilla-Monsalve, Cristina; Trinidad, Oscar; Altamirano-Bustamante, Nelly F.; Altamirano-Bustamante, Myriam M. (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction This systematic review and meta-analysis present a comprehensive evaluation of paper-based microfluidic devices, focusing on their applications in immunoassays. These devices are emerging as innovative solutions to democratize access to diagnostic technologies, especially in resource-limited settings. Our review consolidates findings from diverse studies to outline advancements in paper-based microfluidic technology, including design intricacies and operational efficacy. Key advantages such as low cost, portability, and ease of use are highlighted. Materials and Methods The review categorizes literature based on the design and operational nuances of these diagnostic tools, exploring various methodologies, fabrication techniques, detection methods, and applications, particularly in protein science. The meta-analysis extends to the diverse applications of these technologies, providing a framework for classifying and stratifying their uses in diagnostics. Results and discussion Notable findings include a critical analysis of performance metrics, such as sensitivity and specificity. The review addresses challenges, including the need for further validation and optimization for broader clinical applications. A critical discussion on the validation processes, including cross-validation and rigorous control testing, is provided to ensure the robustness of microfluidic devices. This study offers novel insights into the computational strategies underpinning these technologies and serves as a comprehensive roadmap for future research, potentially broadening the impact across the protein science universe.